Evidence for Elevated Cerebrospinal Fluid ERK1/2 Levels in Alzheimer Dementia. (24th November 2011) - Spitzer, Philipp; Schieb, Heinke; Kamrowski-Kruck, Heike; Otto, Markus; Chiasserini, Davide; Parnetti, Lucilla; Herukka, Sanna-Kaisa; Schuchhardt, Johannes; Wiltfang, Jens; Klafki, Hans-Wolfgang
Abstract : Cerebrospinal fluid (CSF) samples from 33 patients with Alzheimer dementia (AD), 21 patients with mild cognitive impairment who converted to AD during followup (MCI-AD), 25 patients with stable mild cognitive impairment (MCI-stable), and 16 nondemented subjects (ND) were analyzed with a chemiluminescence immunoassay to assess the levels of the mitogen-activated protein kinase ERK1/2 (extracellular signal-regulated kinase 1/2). The results were evaluated in relation to total Tau (tTau), phosphorylated Tau (pTau), and beta-amyloid 42 peptide (A β 42). CSF-ERK1/2 was significantly increased in the AD group as compared to stable MCI patients and the ND group. Western blot analysis of a pooled cerebrospinal fluid sample revealed that both isoforms, ERK1 and ERK2, and low amounts of doubly phosphorylated ERK2 were detectable. As a predictive diagnostic AD biomarker, CSF-ERK1/2 was inferior to tTau, pTau, and A β 42.